2016
DOI: 10.1037/dev0000205
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ early visual attention and social engagement as developmental precursors to joint attention.

Abstract: This study examined infants’ early visual attention (at 1 month of age) and social engagement (4 months) as predictors of their later joint attention (12 and 18 months). The sample (n=325), drawn from the Maternal Lifestyle Study, a longitudinal multicenter project conducted at four centers of the NICHD Neonatal Research Network, included high-risk (cocaine exposed) and matched non-cocaine exposed infants. Hierarchical regressions revealed that infants’ attention orienting at 1 month significantly predicted mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 81 publications
1
21
1
1
Order By: Relevance
“…In a subset of infants who also received a developmental evaluation at 12 months, we found that 3-month attention was associated with both social communication and, to a lesser extent, nonverbal cognitive development. This is somewhat inconsistent with a study by Salley et al (2016) that identified an association earlier in development between 1-month attention and 12-month social communication abilities in a non-ASD sample. It is possible that the present study was simply underpowered to detect this association at this early age.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In a subset of infants who also received a developmental evaluation at 12 months, we found that 3-month attention was associated with both social communication and, to a lesser extent, nonverbal cognitive development. This is somewhat inconsistent with a study by Salley et al (2016) that identified an association earlier in development between 1-month attention and 12-month social communication abilities in a non-ASD sample. It is possible that the present study was simply underpowered to detect this association at this early age.…”
Section: Discussioncontrasting
confidence: 90%
“…Perra and Gattis (2010, 2012) observed a major transition in attentional engagement at 3 months of age, at which time infants increased time spent jointly engaged in object play with a caregiver, followed the attentional focus of a caregiver, and shifted attention between a caregiver and an object, all of which could be argued are foundational skills for the emergence of joint attention. In a recent study, attention skills at a much earlier age, 1 month, were associated with joint attention skills at 1 year of age (Salley et al, 2016).…”
Section: Visual Attention In Early Infancymentioning
confidence: 96%
“…Our results point toward the importance of attention to both people and objects as pre-requisites for joint attention, a foundational process for cognitive and communicative development ( Mundy & Newell, 2007 ; Salley & Colombo, 2016 ; Salley et al, 2016 ). Our findings suggest that 5 months is an important transitional period for sharing attention and are consistent with claims that joint attention might emerge from a developmental progression in which infants first share attention with one social partner (dyadic attention) and later share attention with a social partner and some third object (triadic attention) ( Kaye & Fogel, 1980 ; Salley et al, 2016 ). Our results also indicate that at 5 months, attention sharing is more likely to result from parents’ responding to infants’ attention to objects than infants’ responding to parents’ attention to objects.…”
Section: Discussionmentioning
confidence: 63%
“…The distribution of attention also changes during infancy, from primarily attending to people in the first weeks of life to primarily attending to objects by about the mid-point of the first year ( Bornstein, Cote, & Kwak, 2019 ; Brazelton, Koslowski, & Martin, 1974 ; Johnson, Dzierawiec, Ellis, & Morton, 1991 ; Kaye & Fogel, 1980 ; Peltola, Yrttiaho, & Leppänen, 2017 ). Evaluating infant attention to people versus objects has the potential to yield insights relevant to both typical and atypical development: attention to both people and objects is necessary for sharing attention with a social partner, which in turn plays an important role in cognition and communication ( Klin, Shultz, & Jones, 2015 ; Mundy & Newell, 2007 ; Mundy, 2018 ; Niedzwiecka, Ramotowska, & Tomalski, 2018 ; Peltola et al, 2017 ; Salley & Colombo, 2016 ; Salley et al, 2016 ). In one study evaluating this distribution of infant attention, parents played with their term infant at 2, 3, and 4 months in laboratory-based sessions ( Perra & Gattis, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the mother-child relationship and the type of maternal interaction are extremely important during this period (Haley & Stansbury, 2003;Little & Carter, 2005). The child starts to gain interest in objects and starts to develop an interest in interpersonal play, sharing with the mother the attention toward objects (Gustafsson et al, 2015;Legerstee & Barillas, 2003;Salley et al, 2016). Between the ages of 8 and 12 months, children become more intentionally communicative (Mundy & Willoughby, 1996).…”
Section: Research-article2017mentioning
confidence: 99%